(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
Nutrition is one of the most important factors determining the health of the population. Proper nutrition ensures the growth and development of children, helps prevent diseases, prolongs life, increases labor productivity, and creates conditions for adequate adaptation to the environment. Ensuring healthy nutrition for the younger generation is the most important direction of state policy.